2011
DOI: 10.1021/jo201214x
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Acidity Studies of Dual Hydrogen-Bonding Organic Silanols and Organocatalysts

Abstract: The fundamental properties of a series of organic monosilanols, silanediols, disiloxanediols, and known hydrogen-bonding organocatalysts have been examined in the gas phase using computational and experimental mass spectrometry methods. The organosilicon diol molecules contain dual hydrogen-bonding groups that were designed as potential hosts and hydrogen-bonding catalysts. Newly measured acidities are reported, and implications regarding solvent effects, catalysis, and molecular recognition are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 61 publications
(100 reference statements)
3
32
0
Order By: Relevance
“…[26,27] However in the actual film these terminal hydroxyl moieties crosslink to form siloxane bonds during the curing process. Part A is a viscous silicone polymer with terminal hydroxyl groups.…”
Section: Dtx Stability In Silicone Kit Componentsmentioning
confidence: 99%
“…[26,27] However in the actual film these terminal hydroxyl moieties crosslink to form siloxane bonds during the curing process. Part A is a viscous silicone polymer with terminal hydroxyl groups.…”
Section: Dtx Stability In Silicone Kit Componentsmentioning
confidence: 99%
“…Although disiloxanediols are recognized for their hydrogen‐bonding and anion‐recognition capabilities, they have not been previously reported as anion‐binding catalysts . Anion‐binding catalysis has been identified as an important new mode of catalysis that proceeds by activation of electrophilic ionic substrates by hydrogen bonding to their counter anions .…”
Section: Introductionmentioning
confidence: 99%
“…[10b] Although disiloxanediols are recognized for their hydrogenbondinga nd anion-recognition capabilities, they have not been previouslyr eported as anion-bindingc atalysts. [11] Anionbinding catalysis has been identified asa ni mportant new mode of catalysis that proceeds by activation of electrophilic ionic substrates by hydrogen bonding to their counter anions. [12] Here, we report the synthesis of structurally varied disiloxanediols and the first example of disiloxanediols as an ew class of anion-binding catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Kondo and co‐workers found that certain silanediols fluoresce in the presence of anions 51. In work related to Kondo's reports, the Franz group also explored gas‐phase acidities of several organocatalysts and silanols52 as well as NMR and X‐ray crystallography studies of hydrogen bonding in amide‐containing silanediols 53…”
Section: Silanediol Catalysismentioning
confidence: 99%